PRESENCE OF TRADICIONAL SPANISH LYRIC POETRY IN TWO POEMS OF CESAR CALVO - Cruz Guerrero, Dany Erick (2007)
The Spaniards coming into the New World meant more than just new ways in every·day life. In what regards to literary forms, the Spanish models, which had been highlyperfected after Manrique and the fine expressiveness of Garcilaso at he beginning ofthe XVth century, were transplanted and cultivated with great originality by Sor JuanaInés de la Cruz, and la ter, by Rubén Darío and Vallejo. Calvo· s two poems belong tothat high quality tradition. The purpose of this article is to show this kind of lyricismmanifest and to go along from metrics to the recognition of simílitarities in poetics inorder to better understand Calvo· s sensitiveness.